Effect UV/O3 Modified Rice Husk on the Mechanical Properties of Recycle HDPE Rice Husk Composite / Nishata Royan Rajendran Royan ...[et al.] - Rajendran Royan, Nishata Royan; Sulong, Abu Bakar; Mohd, Nor Yuliana Yuhana; Abdul Ghani, Mohd Hafizuddin; Ahmad, Sahrim (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Modifications of rice husk (RH) surfaces by ultraviolet-ozonolysis (UV/O3) treatment were carried out in order to study the effects on the mechanical properties. The untreated and treated RH was characterized by FTIR, TGA and SEM. Recycled HDPE/RH composites were prepared with five different loading of RH fibers (10, 20, 30, 40 and 50 wt %) using the twin-screw extrusion method. Maleic anhydride grafted polyethylene (MAPE) was added as a coupling agent. Tensile modulus shows an increase trend while tensile strength shows a decline trend with addition of RH loading regardless of treatments. However, composites filled with UV/O3-treated RH give a better result in comparison with composites filled with untreated RH. UV/O3 treatment removes lignin, hemicellulose, fats and waxes from RH surfaces thus giving a rougher surface on RH. Therefore, UV/O3 treatment can be used as an alternative method to modify RH surface in order to improve the adhesion between hydrophilic RH fibre and hydrophobic recycled high-density polyethylene (rHDPE) polymer matrix.